Transient electro-magneto-hydrodynamic two-phase blood flow and thermal transport through a capillary vessel. (December 2016) - Mirza, I.A.; Abdulhameed, M.; Vieru, D.; Shafie, S.
Highlights: Mathematical modeling of electro-magneto-hydrodynamic two-phase blood transport is developed. The motion of blood and particles is controlled by regulating the electrokinetic and magnetic parameters. The thermal transport of blood and particles is controlled by adjusting Joule heating parameter and Eckert number. Blood flow has a pulsating motion and reverse flow is occurring on certain values of K and t parameters. Abstract: Therapies with magnetic/electromagnetic field are employed to relieve pains or, to accelerate flow of blood-particles, particularly during the surgery. In this paper, a theoretical study of the blood flow along with particles suspension through capillary was made by the electro-magneto-hydrodynamic approach. Analytical solutions to the non-dimensional blood velocity and non-dimensional particles velocity are obtained by means of the Laplace transform with respect to the time variable and the finite Hankel transform with respect to the radial coordinate. The study of thermally transfer characteristics is based on the energy equation for two-phase thermal transport of blood and particles suspension with viscous dissipation, the volumetric heat generation due to Joule heating effect and electromagnetic couple effect. The solution of the nonlinear heat transfer problem is derived by using the velocity field and the integral transform method. The influence of dimensionless system parameters like the electrokinetic width, the Hartman number, Prandtl number, the coefficient of heat generation due to Joule heating and Eckert number on the velocity and temperature fields was studied using the Mathcad software. Results are presented by graphical illustrations.